Towards semi-autonomous operation of under-actuated underwater vehicles: sensor fusion, on-line identification and visual servo control - Karras, George C.; Kyriakopoulos, Kostas J.; Loizou, Savvas (My University, 2011)
In this paper we propose a framework for semiautonomous operation of an under-actuated underwater vehicle. The contributions of this paper are twofold: The first contribution is a visual servoing control scheme that is designed to provide a human operator the capability to steer the vehicle without loosing the target from the vision system's field of view. It is shown that the under-actuated degree of freedom is input-to-state stable (ISS) and a shaping of the user input with stability guarantees is implemented. The resulting control scheme has formally guaranteed stability and convergence properties. The second contribution is an asynchronous Modified Dual Unscented Kalman Filter (MDUKF) for the on-line state and parameter estimation of the vehicle by fusing data from a Laser Vision System (LVS) and an Inertial Measurement Unit (IMU). The MDUKF has been developed in order to experimentally verify the performance of the proposed visual servoing control scheme. Experimental results of the visual servoing control scheme integrated with the asynchronous MDUKF indicate the feasibility and applicability of the proposed control scheme. Experiments have been carried out on a small under-actuated Remotely Operated Vehicle (ROV) in a test tank.
Keywords: Parameter estimation; Sensor fusion; Under-actuation; Underwater vehicle; Visual servoing